El Excentrico, 1953-05-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 20, 1953 [20 de mayo de 1953]. Anos 3, No. 14. Cover has a photo of a the court of honor for the 5 de Mayo Fiesta, which was supervised by the Mexican Honor Commission. The woman in the middle was Angelita Primera, who won the title of queen.